2022
DOI: 10.1136/bmjopen-2021-060309
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle risk behaviours among adolescents: a two-year longitudinal study of the impact of the COVID-19 pandemic

Abstract: ObjectiveTo examine changes in the prevalence of six key chronic disease risk factors (the “Big 6”), from before (2019) to during (2021) the COVID-19 pandemic, among a large and geographically diverse sample of adolescents, and whether differences over time are associated with lockdown status and gender.DesignProspective cohort study.SettingThree Australian states (New South Wales, Queensland and Western Australia) spanning over 3000 km.Participants983 adolescents (baseline Mage=12.6, SD=0.5, 54.8% girl) drawn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 44 publications
2
30
1
Order By: Relevance
“…Second, we examined if NSSI independently was associated with covid-19 related stress, even when other variables were controlled for. There is recent empirical support that adolescent girls might be more negatively impacted by the covid-19 pandemic, with a more risky life style [ 8 ], more stress [ 1 ] and increased presentation to health care for self-harm, irrespective of intent [ 48 ], but our results did not support any sex differences in how covid-19 was perceived when symptoms of depression, anxiety and ER difficulties were taken into account.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Second, we examined if NSSI independently was associated with covid-19 related stress, even when other variables were controlled for. There is recent empirical support that adolescent girls might be more negatively impacted by the covid-19 pandemic, with a more risky life style [ 8 ], more stress [ 1 ] and increased presentation to health care for self-harm, irrespective of intent [ 48 ], but our results did not support any sex differences in how covid-19 was perceived when symptoms of depression, anxiety and ER difficulties were taken into account.…”
Section: Discussioncontrasting
confidence: 82%
“…Although less burdened by somatic complications caused by the virus, factors such as societal restrictions, closed schools and family distress have contributed to the lives of children and adolescents being severely affected by covid-19 [ 5 , 6 ]. In adolescents, elevated levels of depression, anxiety and stress, for example, have been found during the pandemic [ 1 , 4 , 7 ], as well as increased risk behaviors [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Crosssectional data from a sample of 983 adolescents indicated increases of excessive recreational screen time (86 to 94%) and insufficient fruit intake (20 to 30%). As well, this data indicated proportions of adolescents engaging in insufficient physical activity (82%) and vegetable intake (84%) remained concerning [3]. The intersection of risk factors for both obesity and mental health demonstrates the need for holistic programs which provide support to improve lifestyle risk factors.…”
Section: Introductionmentioning
confidence: 77%
“…Research has established associations between several lifestyle risk factors, including physical activity, nutrition, sedentary behaviour and sleep that are contributing to the declining physical and mental health status of adolescents [2,3]. Adolescents in high income countries, like Australia are not meeting national guidelines for these risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, COVID-19 restrictions were actualized, and behaviors (including risk behaviors) naturally changed as students adapted to the new environment. Many researchers predicted and reported negative long-term consequences among children and adolescents—particularly excessive recreational screen time, poor diet, physical inactivity, and poor sleep, but also increases in substance use, the prevalence of psychiatric disorders, and suicidal thoughts [ 38 , 39 , 40 , 41 , 42 ]. However, a few reported that restrictions actually resulted in decreases in alcohol consumption and norm-breaking behaviors and that adolescents showed resilience [ 25 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%